TINGKAT PARTISIPASI PETANI DALAM PROGRAM PERLUASAN AREAL TANAM (PAT) KEDELAI (GLYCINE MAX) - Tuti Alawiyah; Ari Tresna Sumantri; Gugun Gunawan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to determine and anylyze the level of farmer participation in the soybean expansion program (PAT) expansion program in sudimanik village, cibaliung sub-district, pandeglang district to know analyze internal factors are related to the level of farmer participation in the soybean expansion program (PAT) expansion . this location research was conducted intentionally in sudimanik village, cibaliung sub-district, pandeglang district, the respondents in this stuy were 36 farmer. The study was conducted in april to july 2018. The reseacrh method used was survey method with descriptive analysis and hypotesis testing using non parametric stastic with test spearman rank corelation.The result of hypotesis testing is that there is a relationship between internal factors of farmers (education level, land area, income and cosmopolitan) and exrternal factors of farmers (extansion intensity and enviromental condition of the farm) with the of farmer participation in PAT soybean program in sudimanik village, cibaliung district pandeglang district participation rate in the planning stage was mostly classified as low (32%), participation in the implementation stage of the result was mostly low (26%), participation in the monitoring phase of activity evaluation was low (25%) and participation in the utilization stage was low (22%)